Assertiveness, self-esteem and violence in the couple in arequipeño university students - Aguirre Quiroz, Lizbeth Alejandra (2024)
Dating violence is one of the most serious and complicated situations which does not obey or consider social, economic and educational criteria. The frequency in which these violent acts are occurring is increasing; However, there are intrinsic factors that can help reduce such risks within relationships. The purpose of this research was to determine the relationship between self-esteem, assertiveness and violence in the couple of university students. For this, an empirical approach of associative strategy and cross-sectional correlational design was chosen, in a sample of 210 participants of both sexes (69.05% women and 30.95% men), between 18 and 25 years old, from a private university in Metropolitan Arequipa. Regarding the evaluation, the Rathus assertiveness scale was used, which was validated in the selected sample, the Rosenberg self-esteem scale and the dating violence questionnaire (CUVINO), all with adequate psychometric properties in the Peruvian population. For the statistical analysis, the Jasp 16.0 program was used, demonstrating as the main result that the greater the person’s assertiveness and positive self-esteem, the fewer the episodes of violence suffered.  As a recommendation, it is necessary to carry out the replicability of studies that verify the relationship between violence, assertiveness and self-esteem, since there are not enough contributions in this regard.